Investigation of Melanin in Dermatophytes that Isolated from Primary Schools Students - Abbas Abdel Hussein Mohi (Journal of Global Pharma Technology, 2016)
The study was conducted on four types of dermatophytes, including Trichophyton rubrub, T. mentagrophytes, Microsporium audouinii and M.canis. For isolated samples from primary school students under the age of sixteen, samples were collected from different areas of tinea capitis, tinea corporis and then identified the fungal infections to distinguish it from, other infections, such as eczema and traditional sensitivity, the diagnosis was done by direct examination of 10% KOH and then SDACC to observe the fungal structures where Morphological Description was identified. The fungus stimulated the production of melanin dye using a PDA medium for the four species. Melanin was detected in two ways copper silver sulfide (AgCuS) and light microscopy where the melanin was presented in the fungal structures of the hyphae and Conidial. The second method was grown for twenty-one days. Melanin was extracted and the melanin concentrations and carefully were observed using the scanning electron microscopy.Keywords: Melanin; Primary school; and Dermatophytes